2018
DOI: 10.1371/journal.pone.0190441
|View full text |Cite
|
Sign up to set email alerts
|

Predicted 10-year risk of cardiovascular mortality in the 40 to 69 year old general population without cardiovascular diseases in Germany

Abstract: AimsTo estimate the 10-year risk of fatal cardiovascular disease (CVD) in the 40 to 69 year old general population in Germany stratified by sex and to analyze differences between socioeconomic status (SES), region and community size in individuals without CVD. The analysis is based on the newly recalibrated SCORE Deutschland risk charts and considered other comorbidities for the classification of the high CVD risk group according to the guidelines of the European Society of Cardiology. Methods and resultsIn 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
5
12
0
Order By: Relevance
“…In Uganda, a large HIV positive cohort population study, showed that men were at high 10-year risk of acute CVD and ART treated populations were more at risk of longer term CVD, as suggested in our study [25]. Of our study patients, 8% were shown to be at greater than a 30% 10-year risk of CVD mortality, similar to what was reported among a general population (5.7% and above) with a comparable age range in Germany and India [50, 51]. We have shown that there is a linear association between older age, patients who have been on ART for longer, and are in the high-risk score band (7.96 ± 4.38 years) compared to very low risk (6.51 ± 3.47 years) for CVD mortality.…”
Section: Discussionsupporting
confidence: 87%
“…In Uganda, a large HIV positive cohort population study, showed that men were at high 10-year risk of acute CVD and ART treated populations were more at risk of longer term CVD, as suggested in our study [25]. Of our study patients, 8% were shown to be at greater than a 30% 10-year risk of CVD mortality, similar to what was reported among a general population (5.7% and above) with a comparable age range in Germany and India [50, 51]. We have shown that there is a linear association between older age, patients who have been on ART for longer, and are in the high-risk score band (7.96 ± 4.38 years) compared to very low risk (6.51 ± 3.47 years) for CVD mortality.…”
Section: Discussionsupporting
confidence: 87%
“…However, all procedures conducted in both groups were identical, and they were treated separately only in analysis. The age of 40 was chosen in order to divide the study sample into younger and older ones, as in a number of studies of cardiovascular risk, the participants aged above 40 are treated as a separate group, as they may develop cardiovascular problems even if not diagnosed [ 12 , 13 ]. Similarly, for the Framingham Heart Study cohort, the age group of participants older than 40 was also analyzed [ 14 ] and some authors even recommend to conduct the formal cardiovascular disease risk assessment, in the case of no risk factors, only for patients at the age of 40 or more [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…26 In Germany, similar results were observed for women but not for men. 27 However, differences in indicators used do assess socioeconomic status do not allow direct comparisons of estimates to be made with our study because they used composite socioeconomic status indicators.…”
Section: Discussionmentioning
confidence: 95%